Pengembangan Aplikasi Batik Khas Tangerang Berbasis Web E-Commerce Menggunakan Metode Waterfall - Bangun Suprianto; Irfan Alamsah; Jepri Afrizal; Khoiriyah; Aries Saifudin (CV. Multi Kreasi Media, 2023)
Presentation of information on the sale of batik products on CV. Ladang Emas Productions, whose user method is in the form of a manual, namely the distribution of product improvements using the media of brochures and asking directly to the company or agency, as a result the news about product sales is still not widespread and is only known by people who are more or less the company. The purpose of creating a webbased sales software design is so that the general public can easily obtain information in the form of product sales. The method used for designing this software uses the waterfall model with an object-oriented system approach that is modeled using UML (Unified Modeling Language). What will happen in the end is that software design means designing a system that can make it easy for consumers to get information on all products being sold so that it becomes efficient for companies and consumers.